Premotor synaptic plasticity limited to the critical period for song learning - Sizemore, Max (National Academy of Sciences, 2011)
Synaptic plasticity has been hypothesized to underlie learning and memory. Understanding of how such plasticity might produce motor learning is limited, in part because of the paucity of model systems with a tractable learned behavior under control of a discrete neural circuit. Songbirds possess both of these traits, thereby providing an excellent model for studying vertebrate motor learning. We report unique evidence of long-term depression (LTD) in the juvenile songbird premotor robust nucleus of the arcopallium (RA). LTD induction at RA recurrent collateral synapses requires NMDA receptors, postsynaptic depolarization, and postsynaptic calcium, and can be reversed by high-frequency stimulation. In adult birds, which have exited the critical period for sensorimotor learning and cannot modify their song, we were no longer able to induce LTD at RA collateral synapses. Furthermore, testosterone-induced premature maturation of song in juveniles abolishes LTD. LTD in nucleus RA therefore makes an excellent candidate mechanism to mediate song learning during development and is well-suited to provide insight into other forms of vertebrate motor learning.